Facile Approach to Synthesize and Characterization of Silver Nanoparticles by Using Mulberry Leaves Extract in Aqueous Medium and its Application in Antimicrobial Activity - Jagpreet Singh; Navalpreet Singh; Aditi Rathi; Deepak Kukkar; Mohit Rawat (Journal of Nanostructures, 2017)
There is a huge demand of silver nanoparticles in the global market due to their special properties and applications in different fields such as nanomedicine , dentists , nanocatalysis, nanoelectronics, textile field, waste water treatment.The major cons of top down and Bottom up methods are the synthesis processes are highly costly, time consuming and many harmful chemicals are used. To reduce these problems Green chemistry comes to play a very important role for making of silver nanoparticles. Use of various plant extracts like leaves, fruits for synthesis of biogenic silver nanoparticles referred as Green Nanotechnology. In the present work we reported the green synthesis of silver nanoparticles using by Mulberry leaves extract without using any toxic chemicals. The Mulberry leaves extract act as reducing agent as well as a stabilizing agent in green nanotechnology process. The making of silver nanoparticles was determined by the change of shade from white to brownish by the addition of Mulberry leaves extract . UV-Vis absorption spectroscopy was used to monitor the measurable formation of silver nanoparticles showed a maximum peak at 440 nm. High resolution Transmission electron microscope confirmed the spherical nature and the highly crystallinity of silver nanoparticles on an average size 15 -25 nm .Antimicrobial activity of the biogenic Ag nanoparticles was performed by a well diffusion method. The nanoparticles exhibited enhanced anti-bacterial activity when incubated in Escherichia Coli and Bacillus Subtilis cultured plates at varied volumes. Current study thus presents a facile and innovative strategy for synthesis of silver nanoparticles.